Kesalahan Penulisan Bahasa Indonesia Pada Mini Research Oleh Mahasiswa Pendidikan Bahasa Indonesia - Nurul Azmi; Feny Nursyahwa Aulia Tarigan; Wisman Hadi (Pusat Riset dan Inovasi Nasional, 2024)
This study analyzes writing errors in the mini research tasks conducted by Indonesian Language Education students at Universitas Negeri Medan. Utilizing qualitative descriptive methods and document analysis, the research identifies writing errors in these tasks. The results indicate a lack of understanding of Indonesian language rules, highlighting the importance of attention to detail in academic writing. These findings are expected to contribute to improving students' academic writing in the future.